2022
DOI: 10.3390/languages7040271
|View full text |Cite
|
Sign up to set email alerts
|

Traceback and Chunk-Based Learning: Comparing Usage-Based Computational Approaches to Child Code-Mixing

Abstract: Recent years have seen increased interest in code-mixing from a usage-based perspective. In usage-based approaches to monolingual language acquisition, a number of methods have been developed that allow for detecting patterns from usage data. In this paper, we evaluate two of those methods with regard to their performance when applied to code-mixing data: the traceback method, as well as the chunk-based learner model. Both methods make it possible to automatically detect patterns in speech data. In doing so, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 79 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…Dabrowska (2014) also showed that a higher frequency threshold leads to more failed derivations, though the difference is rather small. The same finding has been confirmed by Dabrowska & Lieven (2005) and Koch, Hartmann & Quick (2022).…”
Section: Traceback Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…Dabrowska (2014) also showed that a higher frequency threshold leads to more failed derivations, though the difference is rather small. The same finding has been confirmed by Dabrowska & Lieven (2005) and Koch, Hartmann & Quick (2022).…”
Section: Traceback Methodssupporting
confidence: 78%
“…Answering the above questions will also enable discussion of whether the traceback method can be applied to a child's spontaneous speech data from two genealogically unrelated languages. The last question has been posed in several studies (for example Gaskins et al 2022, Koch, Hartmann & Quick 2022, and while the current study sheds some light on that question, it was felt that answering the question properly would warrant a study of its own. This paper is structured as follows.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations